Do sentencing guidelines raise the cost of punishment? - Meade, Jose; Waldfogel, Joel 1962- (1998)
When judges have discretion over fines and prison terms, sentencing exhibits a tendency toward efficiency: fines are larger, and prison terms shorter, for offenders with greater ability to pay. Sentencing guidelines place fairly rigid upper and lower limits on fines and prison terms and may inhibit the achievement of efficiency in sentencing. Preventing judges from substituting fines for prison terms may raise the cost of imposing punishment. The objective of this paper is to measure the efficiency cost of sentencing guidelines using data on federal offenders sentenced" under the Federal Sentencing Guidelines. We find evidence that the guidelines raise the cost of punishment by nearly 5 percent of the total imprisonment cost of federal offenders. Not surprisingly, constraints on cost minimization raise costs.
Keywords: Emprisonnement - États-Unis - Coût - Modèles économétriques; Sentences (procédure pénale) - Aspect économique - États-Unis; Ökonometrisches Modell; Imprisonment -- United States -- Costs -- Econometric models; Sentences (Criminal procedure) -- Economic aspects -- United States -- Econometric models; USA